Business potential in senior services - Nummelin, Johanna (International Journal of Strategic Property Management, 2010)
Europe and generally the western societies are aging rapidly. Public sector in many countries is facing difficulties to keep up the same level of social and health care services as before. The size of younger generations diminishes and the amount of people that need to be supported will increase in relation to working population. Still the challenges that aging society bring are not fully recognized. Beside negative challenges, aging society raises new kinds of opportunities, new business potential. The change will be so rapid that new construction cannot fulfil the need for specialised housing. Moreover, specialized senior housing may not even be what aged consumers want. The biggest market potential can be seen in existing building stock, which needs to be renovated to meet changing needs. Existing building stock has been built for healthy working age generations. Besides renovation, the new needs can be met by new type of services and service concepts. These services are called here senior services. This paper consists of an analysis of different factors that affect demand and supply of senior services. Financing is discussed briefly together with wealth issues. Ideas of new business opportunities have been described following the actor groups and senior service classification.First Published online: 18 Oct 2010